TOXICITY ASSESSMENT OF CARBON NANOTUBES ON ERYTHROCYTE MORPHOLOGY AND LYMPHOCYTES IN VITRO - V, Yuvaraj; S, Rajiv; Mukherjee, Amitava; N, Chandrasekaran; Sastry, Tp (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: Carbon nanomaterials have been used in many biomedical applications due to its unique physical properties. Functionalization of carbon nanotubes (CNT) could improve the physical properties, but pharmacokinetics and toxic effects of pristine and functionalized CNTs, are not well defined. In this study, the toxicity of the pristine and hydroxyl group functionalized Multi‑Walled CNT (MWCNT) compared. Methods: MWCNTs was interacted with human blood. The induced morphological changes in the erythrocytes and cytotoxicity were observed at different concentrations. A thin blood smear was prepared, and the erythrocyte images were obtained using a digital microscope. MTT assay used to assess the cytotoxicity. Results: The result indicate that the pristine MWCNT caused more toxic effects than –OH functionalized MWCNT, which was assessed in terms of changes in the morphology of the erythrocytes and cytotoxicity caused to the lymphocyte cells. Conclusion: The functionalization of MWCNT could reduce the hemotoxicity and improves the biocompatibility. Keywords: Carbon nanotubes, Cytotoxicity, Echinocytes, Erythrocyte, Multi‑walled carbon nanotubes, Lymphocyte.